New Perspective of Eradicating English Functional Illiteracy among University Graduates - Ghoneim, Nahed Mohammed Mahmoud; Elghotmy, Heba Elsayed Abdelsalam (جامعة عين شمس - مركز تعليم الكبار, 2016)
The concept of illiteracy is known as the inability to read or write in any capacity for all practical purposes. English Functional illiteracy is a new and unique one. The functionally illiterate persons can read and possibly write simple sentences with a limited vocabulary, but cannot read or write well enough to manage daily living and employment tasks. The current work sheet sheds light on the importance of eradicating English functional illiteracy as it is considered a vital means of improving prospects for well-paid employment and economic prosperity. The worksheet seeks to illustrate the key success factors in enhancing English literacy in a way that helps to build the capacity to respond to challenges and to modernize the nation.
Keywords: خريجي الجامعات; تعلم اللغة الانجليزية; الأمية الإنجليزية; محو الأمية